Food composition table of selected local tree species in Burkina Faso - Vinceti, Barbara; Fallas Conejo, Diego Alberto; Odongo, Nicanor Obiero; Termote, Céline (2022)
Poor diet quality contributes to stunting in children under five years’, micronutrient deficiencies, overweight/obesity and diet-related non-communicable diseases. Dietary diversity is low in Burkina Faso, where less than 25% of the population meets the minimum dietary diversity recommended. Increasing consumption of fruits, vegetables, nuts, seeds and whole grains increases the likelihood of consuming adequate amounts of the full range of nutrients essential to human health and protects against many forms of non-communicable disease. We compiled food composition data on 97 foods from 37 tree species from Burkina Faso, largely indigenous, with few exceptions, and undomesticated. Data were gathered through an extensive review of the literature and were compiled following international standards.